THE ANALYZE OF FACTORS WHICH IMPACT EMPLOYEE PERFORMANCE WITH WORK SATISFACTION AS INTERVENING VARIABLE AT ROEMANI MUHAMMADIYAH HOSPITAL - Yolanda Ardestya Linanjung; M Fatchurrohman (JASIE, 2023)
Employee is the important something for the realization of organizational goals. In practice, the situation of employee performance is not appropriate with employee and company. This incident is caused by factors which impact employee performance. The factors which impact employee performance are work motivation, organizational culture, work satisfaction, work environment, and work discipline. The aims of this reserach is analyze employee performance which is impacted by work motivation, organizational culture, work environment, work discipline directly and indirectly through work satisfaction. This research is quantitative research. Kind of data which is used in this research are qualitative data and quantitative data. Work motivation has positive and significant impact toward employee performance. Organization culture has negative impact but not significant toward employee performance Work environment has positive and significant impact toward employee performance. Work discipline has positive impact but not significant toward employee performance. Work satisfaction has positive impact but not significant toward employee performance. Work motivation has positive impact but not significant toward employee performance through work satisfaction. Organization culture has negative impact and not significant toward employee performance through work satisfaction. Work environment has negative impact and not significant toward employee performance through work satisfaction. Work discipline has positive impact but not significant toward employee peformance through work satisfaction Abstract consists of background of the study, research method, and finding of the research. Abstract should be no more than 250 words.  Keywords : Employee performance, Work Motivation, Organizational    culture, Work environment, Work discipline, Work satisfaction